Direito à cidade e ao lazer no centro histórico de São Luís do Maranhão - Oliveira, Ariella Silva Fernandes (2024)
This research aims to analyze the effectiveness of the right to leisure in the Historic Center of São Luís through three cultural manifestations present in the neighborhood - Hip Hop, Tambor de Crioula, and Carnival. As the Historic Center of São Luís is the cradle of the city's history and a cultural heritage of humanity, it is necessary to analyze the impact of the transformations of the neighborhood and its heritage status regarding the right to the city and leisure in the studied space. Considering the importance of cultural expressions as forms of identity and leisure for the community inhabiting and frequenting the neighborhood, the research seeks to understand throughout how these manifestations are affected by the impact of urban transformations, preservation policies, and social dynamics, with the aim of reflecting on the importance of accessible leisure for all citizens without distinction